Pengaruh Kemampuan Pemecahan Masalah terhadap Hasil Belajar Matematika - Mar Athul Wazithah (Journal of Mathematics, Statistics and Applications, 2025)
Problem-solving skills is a fundamental cognitive competency in mathematics learning at higher education. This study aims to analyze the effect of problem-solving ability on students' mathematics learning outcomes. The research employed a quantitative approach with ex post facto design involving 29 science education students enrolled in basic mathematics courses. Problem-solving ability was measured using an instrument based on Polya's four indicators (understanding the problem, devising a plan, carrying out the plan, and looking back), while learning outcomes were assessed through achievement tests on basic mathematics content. Data were analyzed using simple linear regression technique. The results showed that problem-solving ability has a significant effect on mathematics learning outcomes with t-value of 4.277 > t-table 2.059 at significance level of 0.05. The regression equation obtained was Y = 3.873 + 1.258X with coefficient of determination (R²) of 0.953, indicating that 95.3% of the variance in mathematics learning outcomes can be explained by problem-solving ability. These findings confirm that problem-solving ability is a primary determinant of students' academic achievement in mathematics and imply the necessity of transforming learning approaches from procedural methods toward problem-solving-based instruction.